Determining population structure and connectivity through otolith chemistry of stout whiting, Sillago robusta. (23rd June 2022) - Sarakinis, Koster G.; Taylor, Matthew D.; Johnson, Daniel D.; Gillanders, Bronwyn M.
Abstract: Fish otoliths encode information on surrounding environmental conditions. This study used otolith chemistry to investigate population structure and potential connectivity in stout whiting ( Sillago robusta ) along the east coast of Australia. Otoliths were analysed for both minor and trace elements, targeting the otolith core (location of birth) and otolith edge (location of capture), along with Ba:Ca transects to investigate life histories. Significant differences were found between core and edge signatures as well as among sample zones for select trace and minor elements. Otolith edge signatures showed evidence of some heterogeneity among zones, likely influenced by both environmental and physiological factors. This combination of factors is reflected in poor separation of sample zones from the multielement analysis, suggesting that future research may benefit from incorporating additional natural markers. Transects reflected some degree of individuality in Ba:Ca profiles, with evidence for potential exposure to upwelling events, or movement from shallow, inshore habitats into deeper waters. The variation in Ba:Ca profiles among fish suggests that populations are comprised of both resident and migratory individuals. While analysis of otolith chemistry could not reliably separate capture locations, patterns in the data suggest that inshore juvenile habitats are likely to be important in supporting exploited populations.